1991
DOI: 10.1093/nar/19.4.939
|View full text |Cite
|
Sign up to set email alerts
|

Selenium induces changes in the selenocysteine tRNA[Ser]Secpopulation in mammalian cells

Abstract: Two isoacceptors of selenocysteine tRNA[Ser]Sec are present in higher vertebrates which are responsible for donating selenocysteine to protein. One such selenocysteine containing protein, glutathione peroxidase, requires selenium for its translation and transcription. Since tRNA[Ser]Sec is a critical component of the glutathione peroxidase translational machinery, the levels and distributions of its isoacceptors were examined from both human and rat cells grown in chemically defined media with and without sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 18 publications
11
104
0
Order By: Relevance
“…Multiple copies of the mouse tRNA [Ser]Sec gene detected in genomic DNA of CHO transfectants+ Genomic DNA was prepared from the indicated CHO cells, digested with EcoR 1, and electrophoresed in 1% agarose+ The DNA was transferred to a Gene Screen Plus hybridization membrane and probed with the 32 P-labeled human tRNA [Ser]Sec gene+ The filter was washed twice in 0+2ϫ SSC, 1% SDS at 65 8C and exposed to X-ray film for 24 h at Ϫ85 8C+ The arrows on the left panel indicate the positions of hybridizing bands representing endogenous CHO tRNA [Ser]Sec sequences in the left and center panels and the arrows on the right panel show the position of the corresponding endogenous sequences in the right panel+ 6-7, 10-11, and 13-14) clearly demonstrate that tRNA [Ser]Sec transcribed from the mouse gene was represented in the fractions containing both isoac- Previously, we have shown that selenium can shift the relative distribution of the tRNA [Ser]Sec population towards the mcm 5 Um-containing isoacceptor when added to either the culture media of mammalian cells (Hatfield et al+, 1991) or Xenopus oocytes (Choi et al+, 1994), or when provided in the diet of rodents (Diamond et al+, 1993;Chittum et al+, 1997)+ As shown in Figure 4, this also occurs when the media of CHO cells is incubated for 10 days with 100 nM sodium selenite+ Transfectants containing elevated levels of tRNA [Ser]Sec , retained principally in the mcm 5 U form, were similarly treated with selenium and the consequences on the distribution of the isoacceptors determined+ As shown in Figure 4 for T10 cells and in both Figure 3 and Table 1 for T6 cells, additional selenium in the media was not capable of stimulating methylation of the mcm 5 U tRNA in transfectants expressing the higher levels of tRNA [Ser]Sec +…”
Section: Overexpression Of Trna [Ser]sec In Cho Cellsmentioning
confidence: 81%
See 3 more Smart Citations
“…Multiple copies of the mouse tRNA [Ser]Sec gene detected in genomic DNA of CHO transfectants+ Genomic DNA was prepared from the indicated CHO cells, digested with EcoR 1, and electrophoresed in 1% agarose+ The DNA was transferred to a Gene Screen Plus hybridization membrane and probed with the 32 P-labeled human tRNA [Ser]Sec gene+ The filter was washed twice in 0+2ϫ SSC, 1% SDS at 65 8C and exposed to X-ray film for 24 h at Ϫ85 8C+ The arrows on the left panel indicate the positions of hybridizing bands representing endogenous CHO tRNA [Ser]Sec sequences in the left and center panels and the arrows on the right panel show the position of the corresponding endogenous sequences in the right panel+ 6-7, 10-11, and 13-14) clearly demonstrate that tRNA [Ser]Sec transcribed from the mouse gene was represented in the fractions containing both isoac- Previously, we have shown that selenium can shift the relative distribution of the tRNA [Ser]Sec population towards the mcm 5 Um-containing isoacceptor when added to either the culture media of mammalian cells (Hatfield et al+, 1991) or Xenopus oocytes (Choi et al+, 1994), or when provided in the diet of rodents (Diamond et al+, 1993;Chittum et al+, 1997)+ As shown in Figure 4, this also occurs when the media of CHO cells is incubated for 10 days with 100 nM sodium selenite+ Transfectants containing elevated levels of tRNA [Ser]Sec , retained principally in the mcm 5 U form, were similarly treated with selenium and the consequences on the distribution of the isoacceptors determined+ As shown in Figure 4 for T10 cells and in both Figure 3 and Table 1 for T6 cells, additional selenium in the media was not capable of stimulating methylation of the mcm 5 U tRNA in transfectants expressing the higher levels of tRNA [Ser]Sec +…”
Section: Overexpression Of Trna [Ser]sec In Cho Cellsmentioning
confidence: 81%
“…Selenium supplementation can increase the levels of tRNA [Ser]Sec isoacceptors (Hatfield et al+, 1991;Baek et al+, 1997)+ Furthermore, as little as 30 nM sodium selenite administered to CHO cells in culture for 3 days can stimulate the levels of the selenoprotein, GPx (Diamond et al+, 1996)+ To determine whether the increased amount of tRNA [Ser]Sec in transfected cells could stimulate GPx levels, transfectants and control cells were assayed for GPx activity, measured in a coupled spectrophotometric assay that quantitates the levels of this enzyme with all other components of the reaction in excess+ As shown in Table 2, elevated levels of tRNA [Ser]Sec did not significantly increase the baseline levels of GPx+ However, CHO cells transfected with a GPx expression construct (Diamond et al+, 1997) produced significantly higher levels of GPx only when the culture media was supplemented with selenium ( Figure 3)+ It remained possible that the levels of selenoproteins other than GPx were being influenced by elevated tRNA [Ser]Sec levels+ To assess this possibility, a CHO transfectant expressing approximately eightfold higher levels of the mcm 5 U isoacceptor was incubated with 75 Se and the labeled selenoproteins were examined by gel electrophoresis and compared to similarly prepared proteins from control cells+ As shown in Figure 5, there is no evidence of elevated steady-state levels of any selenoprotein due to increased levels of tRNA [Ser]Sec + It is unlikely that the reason that elevated levels of tRNA [Ser]Sec obtained following transfection did not alter selenoprotein biosynthesis was a functional defect in the tRNA [Ser]Sec generated from the transfected mouse gene+ As shown in Figure 3, tRNA [Ser]Sec transcribed from the mouse gene was clearly capable of being aminoacylated with serine+ To obtain additional data indicating the functionality of the mouse tRNA [Ser]Sec , tRNA from cells producing the highest levels of tRNA [Ser]Sec (Table 1) were aminoacylated with 3 Hserine and the labeled seryl-tRNAs isolated following RPC-5 chromatography+ The mcm 5 U and mcm 5 Um isoacceptors were independently tested for their ability to respond to UGA in a ribosome binding assay+ As shown in Table 3 (Nirenberg & Leder, 1964) Transcription of tRNA [Ser]Sec is highly atypical in that the primary transcript lacks a 59 leader sequence, that is, transcription begins at the first nucleotide within the gene (Lee et al+, 1987)+ Another unique feature of tRNA [Ser]Sec compared to other tRNAs is that the transcription of tRNA …”
Section: Effects Of Trna [Ser]sec Overexpression On Selenoprotein Biomentioning
confidence: 99%
See 2 more Smart Citations
“…The relative amounts and the distribution of the two isoforms vary in different tissues and cell lines. Selenium supplementation in cell culture as well as in animal models is known to modulate the relative ratios between the two isoforms by inducing the production of mcm 5 Um (70,129,162). The synthesis, function, and regulation of Sec tRNA [Ser]Sec have been reviewed extensively (40,55,128,131 of trsp leads to a selective reduction in selenoproteins such as GPx1, GPx4, and Sep 15, whereas TrxR1 levels are barely affected (190).…”
Section: From Uga To Selenoproteinsmentioning
confidence: 99%